Um som Envolvente: Percepcionar a Interação dos Componentes Espectrais no Espaço Ressonante - Joseph Louis Pablo Wilkinson (2021)
What's sounds relationship with space? Usually when we hear a sound its relationship with space is ignored. But in reality no sound it independe from the space where it travels. What we hear is not only the sound itself but also the influence of space on it. When we listen to a musical performance, its common to appreciate foremost the performer/composer's intention and their effectiveness in conveying it. Natural uncontrollable phenomena is rarely brought to aesthetic focus. This work explore the aesthetic experience from an alternative perspective, in which the artist is put in the background with the role of organiser instead of creator. The practical componente of this work envolves the development of an artistic work in side this framework, using a reverb chamber as focus. My personal experience with the sound and the process of development is documented.